KONFLIK PEMEKARAN WILAYAH DI NANGGROE ACEH DARUSSALAM (NAD) PASCA PERJANJIAN HELSINKI - M. Sahlan Hanafi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
The purposes of this research are to describe the processes of the emerge of ideas to establish the province of ABAS and explain the factors supporting the idea and to explain the reasons of NAD government to reject the expand of ABAS province. Applying qualitative methods using field observation and media discourse study. It was found that media discourse and the proposal for province expand of ABAS rose pro and contra in all level of society that impacted in horizontal and vertical conflict